GP73 reinforces cytotoxic T-cell function by regulating HIF-1α and increasing antitumor efficacy - Xiaoli Yang; Yong Li; Min Min; Nan Jiang; Lijuan Sun; Dandan Zhang; Yuan Cao; Yanhong Zhang; Yufei Wang; Hui Zhong; Xueping Ma; Qi Gao; et al. (Journal for ImmunoTherapy of Cancer)
Background Immunotherapy that targets immune checkpoints has achieved revolutionary success, but its application in solid tumors remains limited, highlighting the need for reliable enhancement of the efficacy of immunotherapy. Golgi protein 73 (GP73), a Golgi membrane protein, has been implicated in various cellular processes, including immune regulation. Recent studies suggested that GP73 may play a role in modulating the immune response in patients with cancer. In this study, we investigated the mechanism by which GP73 regulates T-cell-mediated antitumor immunity within the tumor microenvironment.Methods We used T-cell specific GP73 knockout mice to establish MC38 and B16 tumor models to investigate the impact of GP73-deficient T cells on tumor growth. Single-cell sequencing was subsequently employed to classify tumor-infiltrating immune cells and assess changes in cytokines and metabolic genes. Through RNA sequencing, real-time quantitative PCR, western blotting, flow cytometry, seahorse analysis, glucose uptake, and L-lactic acid secretion assays, we explored how GP73 regulates hypoxia-inducible factor 1α (HIF-1α) to influence T-cell antitumor functionality. Furthermore, we established adoptive transfer experiments to study the ability of GP73-overexpressing T cells to combat tumors. Blood samples of patient with clinical tumor were collected to assess the relationship between immunotherapy efficacy and T-cell GP73 levels.Results In this study, the absence of GP73 in mouse T cells promoted tumor growth and metastasis, accompanied by a decrease in the proportion of cytotoxic CD8+T cell subsets infiltrating the tumor and an increase in exhausted CD8+ T-cell subsets. Further analysis revealed that the effector function of CD8+T cells in tumors relies on glycolysis regulated by HIF-1α rather than immune checkpoints. GP73-deficient T cells exhibit severely impaired glycolysis in hypoxic environments, whereas ectopic GP73 expression restores HIF-1α levels. In adoptive immunotherapy, overexpression of GP73 in T cells inhibits tumor growth. In cytotoxicity assays, knockdown of GP73 affected the ability of CD8+T cells to kill target cells. Clinically, tumor immunotherapy partial response patients present significantly elevated levels of GP73 expression in T cells.Conclusions These findings reveal the role of GP73 in regulating T-cell glycolysis and may lead to new therapeutic strategies for the prognosis and treatment of clinical tumor immunotherapy.